Differences in renal stone treatment and outcomes for patients treated either with or without the support of a ureteral access sheath: the Clinical Research Office of the Endourological Society Ureteroscopy Global Study - Traxer, Olivier; Rassweiler, Jens (World journal of urology, 2015)
PurposeTo describe the differences in the treatment and the outcomes of renal stones treated with flexible ureteroscopy (URS) either with or without the support of a ureteral access sheath (UAS).MethodsThe Clinical Research Office of the Endourological Society URS Global Study involved the collection of prospective data from consecutive patients treated with URS at centers around the world over a 1-year period. Baseline characteristics, stone location, treatment details, postoperative outcomes and complications were recorded. Inverse-probability-weighted regression adjustment (IPWRA) analyses were conducted on outcome from patients treated with or without the use of a UAS to determine the impact on stone-free rates (SFRs).ResultsOf 2239 patients treated with flexible URS, 1494 (67 %) patients were treated with the use of a UAS and 745 (33 %) without a UAS. The IPWRA analyses conducted on 1827 patients with complete data and based on treatment and outcome models showed that if URS procedures were performed without the use of an UAS, the average stone-free rate would be 0.504 compared with 0.753 with a UAS. This average treatment effect of 0.248 was not significant (P = 0.604). Using IPWRA analysis on only the treated population in the estimations revealed no significant difference between using and not using a UAS (31 %; ATET: 0.311; P = 0.523).ConclusionsThe study showed no difference in SFR when a UAS was used or not. Whereas UAS did not increase the risk of ureteral damage or bleeding, postoperative infectious complications were reduced.